El clima organizacional y su incidencia en el desempeño laboral del personal docente de la unidad educativa José María Velasco Ibarra de la ciudad de Milagro - Andrade Mosquera, Marjorie Alexandra (2015)
An organization is an open system that develops the same from external stimuli and internal processes of its corporate bodies, leaders must strive to create the ideal environment for achieving the objectives of the organization. In all these respects we can say that there is disagreement both administrative staff as a teacher; however, through motivational activities may improve the organizational environment. To strengthen relationships an improvement plan proposed organizational climate to increase job performance of workers of the Education Unit "José María Velasco Ibarra" Milagro city……